Analysis of Internet Quality Improvement from HFC to FTTH in Housing X - Elfrida, Carissa; Fauzi, Ahmad; Setyowati, Endah (Sistemasi: Jurnal Sistem Informasi, 2025)
The demand for fast, stable, and reliable internet services continues to grow, particularly in densely populated residential areas. One of the ongoing issues is the limitations of Hybrid Fiber Coaxial (HFC) networks, which often result in low speeds, high latency, and unstable connections. This study aims to analyze the improvement in internet quality resulting from the migration from HFC to Fiber to the Home (FTTH) in Residential Area X, East Jakarta. A quantitative approach was employed, involving direct measurements on 100 homepasses before and after the migration. The parameters analyzed include download and upload speeds, latency, jitter, packet loss, Power Link Budget, Optical Power Budget, Round Trip Time (RTT), and Quality of Service (QoS) metrics. The results show a significant improvement in internet performance after the migration to FTTH. The average download speed increased from 16.75 Mbps to 128.79 Mbps, while the upload speed rose from 2.99 Mbps to 54.53 Mbps. Latency decreased from 66.23 ms to 5.73 ms, jitter dropped from 12.37 ms to 2.55 ms, and packet loss was reduced from 3.06% to 0.47%. Although FTTH has a lower power budget compared to HFC, the Power Link Budget analysis indicates that the network quality delivered by FTTH is more stable and reliable. These findings confirm that FTTH provides a significantly more stable and dependable internet connection than HFC.